INTEGRASI PEMBELAJARAN GUIDED DISCOVERY DALAM MODUL SPERMATOPHYTA UNTUK MAHASISWA PENDIDIKAN BIOLOGI - Nugroho, Anwari Adi; Subiyantoro, Singgih (Jurnal Pendidikan Matematika dan IPA, 2018)
Guided discovery learning is a learning that invites students to actively discover the concept / knowledge through a series of activities. Guided discovery learning can be integrated in teaching modules to make learning more effective and self-reliant. This study aimed to integrate guided discovery learning in spermatophyta module for biology education students. This research is an explorative research with stages include curriculum analysis, subject matter analysis, learning model analysis, and integration of learning model in the Module. Data source in the form of book document, expert opinion, and spermatophyta module. Data analysis used qualitative descriptive analysis. Based on the analysis result, it is found that guided discovery guided discovery integrated in module include stimulation, problem statement, data collection, verification, generalization . The guided discovery guided synthesis is integrated into 3 subspaces on spermatophyta material 1) classification, determination, and nomenclature of plants, 2) spermatophyta (seed plants); 3) high plant herbarium. Integration of guided discovery learning on unified modules integrated in the module component of learning activities.Keywords: Guided discovery, Spermatophyta Module